Logic, Language, Information, and Computation 29th International Workshop, WoLLIC 2023, Halifax, NS, Canada, July 11-14, 2023, Proceedings - Hansen, Helle Hvid.; Scedrov, Andre; de Queiroz, Ruy J.G.B. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
Edited in collaboration with FoLLI, the Association of Logic, Language and Information this book constitutes the refereed proceedings of the of the 29th International Workshop on Logic, Language, Information, and Computation, WoLLIC 2023, held in Halifax, NS, Canada, during July 11-14, 2023. The 24 full papers (21 contributed, 3 invited) included in this book were carefully reviewed and selected from 46 submissions. The book also contains the abstracts for the 7 invited talks and 4 tutorials presented at WoLLIC 2023. The WoLLIC conference series aims at fostering interdisciplinary research in pure and applied logic.
Learning Context-Free Grammars from Positive Data and Membership Queries -- The Web Still Needs Logic and Reasoning: A Short Introduction to SHACL for Logicians -- From Gödel's Incompleteness Theorem to the completeness of bot beliefs -- Quantitative Global Memory -- Effective Skolemization -- Factive Complements are not Always Unique Entities: A Case Study with Bangla 'remember' -- Two-layered logics for paraconsistent probabilities -- An Axiom System for Hybrid Logic with Propositional Quantifiers -- An Evidence Logic Perspective on Schotch-Jennings Forcing -- A separation logic with histories of epistemic actions as resources -- Conditional Obligations in Justification Logic -- Structural Completeness and Superintuitionistic Inquisitive Logics -- Validity in Choice Logics - A Game-theoretic Investigation -- Aleatoric Propositions: Reasoning about Coins -- Towards an induction principle for nested data types -- A principled approach to Expectation Maximisation and Latent Dirichlet Allocation using Jeffrey's update rule -- Parameterized Complexity of Propositional Inclusion and Independence Logic -- Parallelism in Realizability Models -- Bisimulations between Verbrugge models and Veltman models -- Focus-style proofs for the two-way alternation-free $\mu$-calculus -- Relevant Reasoning and Implicit Beliefs -- Decidability of modal logics of non-k-colorable graphs -- Subsumption-Linear Q-Resolution for QBF Theorem Proving -- Maximally Multi-Focused Proofs for Skew Non-Commutative MILL.
Keywords: Logic; Logic